Forest Influences and Research Needs Thereof in India - Dabral, B. G. (Indian Forester, 1961)
Research work on Forest Influences is to evaluate the significance of the effects resulting from the presence of forests upon climate, soil water, run-off, streamflow, soil productivity and to understand their relation to the aspects of succession, natural reproduction, cutting, fire and the management of forest for their climatic and watershed values. The results of research done on regional basis should be applied for appropriate remedial measures for deteoriated and damaged watersheds as well as towards maintenance of the health and hygiene of properly functioning watersheds. The interpretation of forest influences should take into consideration the entire watershed as a living unit and should not be limited to the different components which constitute it.